Partial sequence conservation of SARS‐CoV‐2 NSP‐2, NSP‐12, and Spike in stool samples from Abadan, Iran. (21st April 2022) - Zandi, Milad; Soltani, Saber; Tabibzadeh, Alireza; Nasimzadeh, Sepideh; Behboudi, Emad; Zakeri, Armin; Erfani, Yousef; Salmanzadeh, Shokrollah; Abbasi, Samaneh
Abstract: Since the onset of the coronavirus disease 2019 (COVID‐19) pandemic, the clinical manifestations of the virus have undergone many changes. Recently, there have been many reports on gastrointestinal symptoms in COVID‐19 patients. This study is aimed to perform a detailed phylogenetic study and assessment of different SNVs in the RNA genome of viruses isolated from fecal samples of patients with COVID‐19 who have gastrointestinal symptoms, which can help better understand viral pathogenesis. In the present study, 20 fecal samples were collected by written consent from COVID‐19 patients. According to the manufacturer's protocol, virus nucleic acid was extracted from stool samples and the SARS‐CoV‐2 genome presence in stool samples was confirmed by RT–PCR assay. Three viral genes, S, nsp12, and nsp2, were amplified using the reverse transcription polymerase chain reaction (RT–PCR) method and specific primers. Multiple sequencing alignment (MSA) was performed in the CLC word bench, and a phylogenetic tree was generated by MEGA X based on the neighbor‐joining method. Of all cases, 11 (55%) were males. The mean age of the patients was 33.6 years. Diabetes (70%) and blood pressure (55%) were the most prevalent comorbidities. All 20 patients were positive for SARS‐CoV‐2 infection in respiratory samples. Molecular analysis investigation among 20 stool samples revealed that the SARS‐CoV‐2 genome was found among 10 stool samples; only three samples were used for sequencing. The polymorphism and phylogenetic analysis in SARS‐CoV‐2 showed great similarity among all of the evaluated genes with the Wuhan reference sequence and all of the current variants of concern (VOCs). The current study represents a great similarity in polymorphism and phylogenetic analysis of the SARS‐CoV‐2 isolates with the Wuhan reference sequence and all of the current VOC in the particular evaluated partial sequences of S, nsp12, and nsp2. Abstract : Schematic of different steps of methodology.